Imbalance of Controlled Death in Peripheral Blood Lymphocytes in Crohn’s Disease and Ulcerative Colitis - Dudzińska, Ewa; Szymona, Kinga; Gil-Kulik, Paulina; Chomik, Piotr; Świstowska, Małgorzata; Gryzińska, Magdalena; Kocki, Janusz (Medicina (Kaunas, Lithuania), 2019)
Background and objectives: Inflammatory bowel disease (IBD) mainly includes Crohn’s disease (CD) and ulcerative colitis (UC). Both conditions are associated with an exacerbated intestinal immune response to harmless stimuli, leading to upregulation of pro-inflammatory mediators. Materials and Methods: The subjects of the study were 55 patients with IBD. The control group consisted of 35 healthy subjects. The researched material consisted of peripheral blood lymphocytes collected from the subjects. Expression of the genes BAX, BCL2, CASP3 and CASP9 was assessed at the mRNA level in the peripheral blood lymphocytes of patients with ulcerative colitis and Crohn’s disease relative to the healthy subjects. The expression of the genes was determined by rtPCR using TaqMan probes specific for these genes. Results: The group of patients diagnosed with CD had statistically significantly higher expression of the genes BAX (p = 0.012), BCL2 (p = 0.022), CASP3 (p = 0.003) and CASP9 (p = 0.029) than healthy subjects. Expression of BAX, BCL2, CASP3 and CASP9 in UC patients in the active phase of the disease was significantly lower than in patients in remission: BAX (p = 0.001), BCL2 (p = 0.038) and CASP9 (p = 0.007). In patients with UC, the BAX/BCL2 ratio was significantly correlated (r = 0.473) with the duration of the disease. In the group of CD patients treated biologically, a significantly lower BAX/BCL2 ratio was demonstrated than in patients that were not biologically treated. Conclusions: Our research has shown a simultaneous increase in the expression of the anti-apoptotic BCL2 gene and the proapoptotic BAX gene, which suggests the dysregulation of apoptosis mechanisms in IBD. Significantly higher expression of BAX and BCL2 in UC patients in remission as compared to CD may suggest differences in these diseases in terms of prognosis and treatment. Our results may suggest that an underlying imbalance in factors controlling apoptosis in peripheral blood lymphocytes may be the response of the immune system to inflammation of the intestinal mucosa. Modulation of apoptosis may become an important therapeutic mechanism in IBD.